Exploratory Walk as a Method of Studying Urban Tourism Space: A Case of Charles Bridge in Prague - Bazuń, Dorota; Kwiatkowski, Mariusz (Journal of Tourism, Sustainability and Well-being, 2020)
The purpose of this article is to characterise the concept and discuss the possibilities of applying exploratory walking as a method of research in urban tourism spaces. In the article, the original concept of the method is characterised and discussed based on a pilot study. The place chosen for the pilot study is Charles Bridge in Prague. The conclusions about further work on improving the method and adapting it to the research needs related to the use of urban spaces by tourists are confirmed. Such walks can be a useful research method and a potential tool for recognising and introducing social and spatial changes. The exploratory walks help to obtain more material than sedentary interviews. Despite the positive functions of the walks, the pilot study also showed that the method could not function alone. Other methods and techniques should complement it. The analyses in the article method can contribute to a better understanding of the phenomena and processes observed in urban tourist spaces, as well as to the design and implementation of changes serving improving tourist services.